An Analysis of EFL Teachers’ Fear of Failure as Their Motivation for Pursuing Graduate Studies - Le, Thanh Thao; Trinh Quoc, Lap (FOSTER: Journal of English Language Teaching, 2021)
Many studies have been conducted to clarify the impact of teachers’ motivation for participating in TPD activities; nevertheless, none of them has viewed teachers’ fear of failure as their motivation for TPD, especially for pursuing graduate programs in the Vietnamese context. That explains why this current qualitative study with the participation of nine EFL teacher interviewees was administered to fill in the abovementioned gap. Moreover, the study was conducted in a tertiary institution in the Mekong delta of Vietnam. Based on the data analysis, several teachers’ fears of failure as their motivation for following graduate programs were detected. Their fears included self-perceived inadequate qualifications in TEFL which resulted in their ineffective teaching performances. Participants were also much concerned about losing a job, failing to have opportunities to further their education and losing momentum for work due to routinized teaching. Mid- age job crisis, negative effects of lacking role models on the growth of children and other younger people, lack of collegial support, and low self-confidence were found to be motivating fears which stimulated participants to make them pursue higher degree programs. The paper ends with discussions of the findings and pedagogical implications